PAJAK DAERAH dan PENGARUHNYA TERHADAP PDRB di PROPINSI KALIMANTA TIMUR - Dwika Julia Mutiara (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2015)
This study aims to see the influence of local taxes, retribution, capital expenditure and labor force participation rates on regional gross domestic product in the District/Municipalities of East Kalimantan Province period 2004-2013. This study uses panel data by selecting best model that is the Fixed Effects Model (FEM). The results show that the variables of local taxes and retribution have a significant effect and has positive relationship to regional gross domestic product, while capital expenditure have no significant effect on regional gross domestic product. For variable labor force participation rate (LFPR) is significantly influence but negative correlation to the regional gross domestic product . Based on the results obtained by the coefficient determination of 98,42% variable means of local taxes, levies, capital expenditures and LFPR in this study may explain the dependent variable is the regional gross domestic product.DOI: 10.15408/sjie.v4i1.2296